2013
DOI: 10.1177/0009922813492880
|View full text |Cite
|
Sign up to set email alerts
|

Is Bigger Really Better? Obesity Among High School Football Players, Player Position, and Team Success

Abstract: Objective. American football is one of the most common high school sports in the United States. We examine obesity among high school football players, and variations based on positions, team division, and team success. Patients and methods. We used 2 data sets from the North Carolina High School Athletic Association (n = 2026) and MaxPreps (n = 6417). We examined body mass index, calculated using coach-reported height and weight, by player position, division, and success based on win–loss percentage. Results. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 43 publications
0
8
0
1
Order By: Relevance
“…However, a prior publication from our group suggests that increasing athlete BMI does not significantly improve team success. 8 Improved team success in high school football would be a small reward for accepting the well-documented risks of adolescent obesity, and without even this incentive, one is left only with the dangers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a prior publication from our group suggests that increasing athlete BMI does not significantly improve team success. 8 Improved team success in high school football would be a small reward for accepting the well-documented risks of adolescent obesity, and without even this incentive, one is left only with the dangers.…”
Section: Discussionmentioning
confidence: 99%
“…5-7 A prior study from our group demonstrated a similar pattern among high school football players in the state of North Carolina, and Kropa et al again identified such findings in urban adolescents receiving pre-participation physical evaluations. 3,8 No studies yet have confirmed this finding to be consistent among high school football players nationwide, nor has the problem of obesity been compared across sports.…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37] Height in adults cannot, in principle, be modified by exogenous factors such as training and diet. As such, the heights of tight ends and offensive and defensive linemen, which exceed the population mean by 3 in (7.6 cm) or more, are explained by selective recruiting of players with these height characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…The fitness argument is further undermined by preliminary evidence that obesity is more common in youth football players than in normative samples of age-, race-and sex-matched children [17]. While that study had some shortcomings, we believe its main message likely is correct given that the finding persists in more diverse populations of football players as they mature in that sport, through high school [25], college [30] and even at the professional level [4]. Other serious health risks appear in football players at unusually young ages; one study found metabolic syndrome in nearly 20% of collegiate football players [30], and studies on professionals and retired pros found even-more severe health problems [14,24,29], despite those athletes presumably having the best access to trainers, dietary advice, and the ability to focus full-time on physical fitness.…”
mentioning
confidence: 91%